A Novel Adjustable Damper Design for a Hybrid Passive Ankle Prosthesis - Amirreza Naseri; Majid Mohammadi Moghaddam; Mohammad Gharini; Maziar Ahmad Sharbafi (Actuators, 2020)
Specifications of actuators when interacting with biological systems such as the human body are entirely different from those used in industrial machines or robots. One important instance of such applications is assistive devices and prostheses. Among various approaches in designing prostheses, recently, semi-active systems attracted the interest of researchers. Even more, some commercial systems benefit from designs such as implementing an adjustable damper in the ankle prosthesis to increase range of motion. The main reason for adding damper is to assist amputees’ walking locomotion on slopes (especially downward). In this paper, we introduce a hydraulic damper design for use in the transtibial prosthetic foot. In the fabricated hydraulic prosthetic foot, two one-way flow control valves are exploited to tune the damping ratio in the plantar flexion and dorsiflexion, independently. Using the carbon prosthetic foot in series to a damper and spring could improve mimicking intact foot movement. First, we present the details of the damper and the prosthesis mechanical design. Then, we introduce experiment-based modeling for the damper’s conceptual design in the proposed prosthesis using SIM-Hydraulic and MATLAB. This device is fabricated and tested in a pilot experiment. The compact design with reduced weight and size of the prosthetic foot are additional advantages of the proposed prosthetic foot.